How the program M-files affects the knowledge management within a company: A case study - Rasmus, Sofie (My University, 2015)
This Master´s Thesis examines how the implementation of a new document and enterprise content management solution program called M-files affects the knowledge management within the company Oy M.Rauanheimo Ab. The main purpose of this study is to create a deeper knowledge of the topic knowledge management. A secondary purpose is to study how it is visible in the company Oy M.Rauanheimo Ab and to explore how the implementation of the program M-files affects the knowledge management within the company. This study is done to enhance the understanding of Knowledge Management in practice, how is this shown in real life companies. The methods used have been desk studies, actively participating in the implementation process, benchmarking and though interviews done at Oy M.Rauanheimo Ab. One of the major theories used have been the SECI-model and the enabling conditions for this model has been thoroughly examined within the company The program was at the time of the interviews not fully implemented, and as a result, some predictions of the implementation of M-files have been made. M-files will give the company a tool for collecting lessons learned/ best practices, which is beneficial for knowledge management. It will also ease the knowledge flow, both horizontally and vertically. Hopefully, it creates a base for handling new ideas in the company and the systematic knowledge assets can be improved by this program. It will also affect the SECI-model positively.
Keywords: Knowledge Management; Organizational Knowledge Creation; SECI-model; M-files; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|